ICTs for Improving Patients Rehabilitation Research Techniques Second International Workshop, REHAB 2014, Oldenburg, Germany, May 20-23, 2014, Revised Selected Papers - Fardoun, Habib M.; R. Penichet, Victor M.; Alghazzawi, Daniyal M. (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed proceedings of the second International Workshop on ICTs for Improving Patients Rehabilitation Research Techniques, REHAB 2014, held in Oldenburg, Germany, in May 2014. The 26 revised full papers presented were carefully reviewed and selected from 69 submissions. The papers focus on virtual and enhanced environments, covering topics such as motor rehabilitation; neuroimaging in rehabilitation; virtual rehabilitation; clinical assessment; cognitive rehabilitation; communication and language; ambisonics and audio environments; haptic devices; sensory impairment; medical systems; input devices; sensors and actuators; multi-user systems for user interaction; computer access; virtual humans; balance, posture and mobility; communications aids; tools for architectural/CAD design; product design, testing and prototyping; training tools for rehabilitation; augmented reality applications; human factors; rehabilitation robotics.